ANALISIS TENTANG HUKUM PERPAJAKAN DI INDONESIA MENURUT HUKUM ISLAM - Suhadi dan Santoso (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2013)
Tax law in Indonesia has a clear hierarchy in order: the 1945 Constitution, the Bill, Government Regulation, Decree of the President and so on. This hierarchy is executed strictly. Lower level regulations must not conflict with higher-level rules. Taxes are one of the country's financial problems. Regulation used by government to regulate the country's financial problems, is Article 23A of the 1945 Constitution (taxes and other fees for the purposes of coercive state governed by law). Contrary to the efforts and hard work of director general of taxes, and of course the taxpayer compliance in meeting their tax obligations, was the careless use of the tax revenue as they should. Money that has been collected with great difficulty, is not used wisely, especially taking into account the priorities and multiplier effects. It seemed the money is used for business-related allowances for state officials. In this regard, Islam as ad-din (religion) has set rules governing the procedures of the relationship between man and al-Khaliq (God) and relations among humans (mu'amalah) in all aspects. These aspects are economic, political, social, cultural, state defense and security, technology and others. In the economic field (majal iqtishadi), Al-Quran and Hadith regulate how individual and state gather income (mawarid). This is also to fulfill the various needs of all human (collective). These include both personal needs and the needs of the country. Fulfillment of various requirements is necessary to devoted completely to God.Tax (dharibah) is one form mu'amalah in economics, as a means of fulfilling the needs of the state and society to finance public needs such as safety, health, and education. Even though the tax is allowed by ulama, the implementation should be in accordance with Shariah guidelines. Otherwise, the tax would come out of the track as a means of meeting the needs of the state and society rather become oppressive tool of the ruler to the people. Keywords: Tax Law, Tax, Islamic Law.